2015
DOI: 10.5194/acp-15-4997-2015
|View full text |Cite
|
Sign up to set email alerts
|

Observations of planetary waves in the mesosphere-lower thermosphere during stratospheric warming events

Abstract: Abstract. This study investigates the effect of stratospheric sudden warmings (SSWs) on planetary wave (PW) activity in the mesosphere-lower thermosphere (MLT). PW activity near 95 km is derived from meteor wind data using a chain of eight SuperDARN radars at high northern latitudes that span longitudes from 150 • W to 25 • E and latitudes from 51 to 66 • N. Zonal wave number 1 and 2 components were extracted from the meridional wind for the years 2000-2008. The observed wintertime PW activity shows common fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 25 publications
(63 reference statements)
6
77
0
Order By: Relevance
“…Here we separate Arctic winters that exhibit a substantial mesospheric response to SSWs from years without such a response. We employ the conventions originally outlined by Tweedy et al () and later applied by Stray et al (), Limpasuvan et al (), and Harvey et al () to define SSW winters with an elevated stratopause (ES) event (see Manney et al (, ) and Tomikawa et al () for a detailed description of the observed meteorology during these events). Specifically, Arctic winters are considered to have an ES if they satisfy the following three criteria: (1) easterlies at the stratopause from 70°–90°N for five or more days, (2) 70°–90°N temperature is below 185 K, and (3) the polar stratopause “jumps” 10 km or more in altitude from its climatological altitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we separate Arctic winters that exhibit a substantial mesospheric response to SSWs from years without such a response. We employ the conventions originally outlined by Tweedy et al () and later applied by Stray et al (), Limpasuvan et al (), and Harvey et al () to define SSW winters with an elevated stratopause (ES) event (see Manney et al (, ) and Tomikawa et al () for a detailed description of the observed meteorology during these events). Specifically, Arctic winters are considered to have an ES if they satisfy the following three criteria: (1) easterlies at the stratopause from 70°–90°N for five or more days, (2) 70°–90°N temperature is below 185 K, and (3) the polar stratopause “jumps” 10 km or more in altitude from its climatological altitude.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is a significant mesospheric response during 22% of major SSW days (e.g., Zülicke et al, ) and this response is well reproduced by WACCM (Limpasuvan et al, , ). In particular, the model captures observed mesospheric cooling and wind reversals (e.g., Eswaraiah et al, ), enhanced PW activity in the MLT (Chandran, Collins, et al, , Chandran, Garcia, et al, ; Stray et al, ), and observed enhancements in nighttime ozone at the secondary ozone maximum (Tweedy et al, ). However, to date there has not been a comprehensive evaluation of mesospheric polar vortex characteristics in WACCM, nor the response of the mesospheric polar vortex to SSWs.…”
Section: Introductionmentioning
confidence: 93%
“…Model fields are output every 3 h. For each run, ES‐SSW events are identified following the three criteria used by Stray et al . []. Based on the polar cap averaged (70°N to 90°N) zonal‐mean zonal wind and zonal‐mean temperature between October and May of each winter, we require that (1) the temperature between 80–100 km falls below 190 K, (2) the reversal of the zonal‐mean zonal wind from eastward to westward direction at the 1 hPa level (~50 km) persists for longer than 5 days, and (3) the stratopause altitude, based on the zonal‐mean temperature maximum between 20 km and 100 km, as discussed by Tweedy et al .…”
Section: Model and Methodologymentioning
confidence: 99%
“…Apart from direct enhancements of stratospheric temperatures, SSWs have been demonstrated to affect planetary wave activity even extending into the opposite hemisphere (e.g. Stray et al, 2015). If such effects were capable of, for example, triggering the springtime breakdown of the polar vortex, associated horizontal transport of stratospheric ozone would contribute to determination of the tropopause altitude (e.g.…”
Section: Discussionmentioning
confidence: 99%